Soil Fertility Status and The Effect of Organic Fertilizers on Onion Growth (Allium Ascalonicum L) - Ahmad Rasyid; Iswahyudi Iswahyudi; Cut Mulyani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
This study aims to determine the status of soil fertility and the effect of organic fertilizer on the growth of shallot plants. This study used a non-factorial Randomized Block Design (RBD), which consisted of 7 levels, namely: O0: No organic fertilizer (control), O1: chicken manure, O2: cow manure, O3: goat manure, O4: petroganic fertilizer, O5: sheep manure, O6: palm oil and sugarcane waste fertilizer. The observed variables were the physical and chemical properties of the soil as well as the soil fertility status of the study site as well as the height and number of leaves of shallot plants measured at the age of 20, 40 and 60 Days After Planting (DAP). The results showed that the soil fertility status in the study area was included in the very low fertility class. The type of organic fertilizer treatment had a very significant effect on the height and number of leaves of shallot plants at the age of 30 and 45 DAP and had no significant effect on the age of 15 DAP. The best results were obtained in the treatment of giving chicken manure (O1).